Public Law, Legitimacy and Indigenous Aspirations - Hobbs, H (Bloomsbury Publishing, 2020)
Over the last several years, the Australian community has debated whether and how to recognise Aboriginal and Torres Strait Islander peoples in the Australian Constitution. Following the Uluru Statement from the Heart and the Referendum Council’s Final Report, the question of constitutional reform has coalesced around the idea of a ‘First Nations Voice’, which would empower elected Aboriginal and Torres Strait Islander representatives to advise Parliament on all matters affecting Indigenous peoples. The idea is still in its infancy and many details are yet to be finalised, including even whether a referendum will be held. However, the proposed First Nations Voice gives rise to a more fundamental question concerning public law’s relationship with Indigenous law, rights and culture. Article 18 of the United Nations Declaration on the Rights of Indigenous Peoples, endorsed by Australia in 2009, provides that Indigenous peoples have the right ‘to maintain and develop their own indigenous decision-making institutions’. This article maintains that the form of those institutions must reflect Indigenous peoples’ values, character and knowledge. The problem is, as Indigenous and non-Indigenous scholars have long remarked, accommodating Indigenous forms of decision-making within the political and legal architecture of the state necessarily involves transforming them in some manner. How does this occur in practice, and does it—like Kanien’kehaka scholar Taiaiake Alfred suggests—mean Indigenous self-governance is ‘meaningless’? This paper examines two institutional forms aimed at providing Indigenous peoples with the capacity to have their voices heard in the processes of settler-state government. In exploring the Aboriginal and Torres Strait Islander Commission and the Canadian territory of Nunavut, this paper assesses whether and to what extent their form and operation was built on cultural principles, processes and knowledge distinct to the respective Indigenous nations. In doing so, this study articulates problems and pitfalls to be avoided in designing a culturally appropriate First Nations Voice within Australia’s public law framework. Its goal, however, is not to interrogate Indigenous decision-making institutions, but to challenge public law. It aims to make public law’s boundaries porous; so that public law can accommodate Indigenous institutions of decision-making in Indigenous forms, language, and voice, rather than simply transforming them into the settler-state’s image.